PERAN GURU PAI DALAM PEMBINAAN MODERASI BERAGAMA PESERTA DIDIK DI SMK NEGERI 1 LUMUT KABUPATEN TAPANULI TENGAH - Hafizur Rohim Nasution; Dedi Masri; Humaidah Br. Hasibuan (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2025)
A multicultural school environment requires the cultivation of tolerance and a balanced religious attitude to prevent potential conflicts and radicalism among the youth. This study aims to describe and understand the role of Islamic Religious Education (PAI) teachers in fostering moderate religious attitudes among students at SMK Negeri 1 Lumut, Tapanuli Tengah Regency. This study employed a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation studies, involving PAI teachers, the school principal, other subject teachers, and students from various religious backgrounds as informants. The data were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing. The findings indicate that PAI teachers play a vital role as educators, mentors, role models, and facilitators of interfaith dialogue. Through exemplary behavior, contextual learning approaches, and social activities, PAI teachers successfully inculcate the values of wasathiyah (balance), tasamuh (tolerance), and musawah (equality). However, some constraints remain, including limited learning time, differences in family upbringing, and the absence of structured, sustainable interfaith activities. PAI teachers hold a strategic role in building a moderate culture within the school environment, which can be optimized through better collaboration between teachers, school authorities, and the community.